Study on the oxidation of copper nanowire network electrodes for skin mountable flexible, stretchable and wearable electronics applications - Hong, Insic; Lee, Seunggon; Kim, Dongkwan; Cho, Hyunmin; Roh, Yeonwook; An, Hyeongi; Hong, Sukjoon; Ko, Seung Hwan; Han, Seungyong (Nanotechnology, 2019)
Copper nanowires (Cu NWs) are suitable material as an electrode for flexible, stretchable and wearable devices due to their excellent mechanical properties, high transparency, good conductivity, and low cost, but oxidation problem limits their practical use and application. In order to use Cu NWs as an electrode for advanced flexible, stretchable and wearable devices attached directly to the skin, the influence of the body temperature on the oxidation of Cu NWs needs to be investigated. In this paper, the oxidation behavior of Cu NWs at high temperature (more than 80 °C) as well as body temperature is studied which has been remained largely questionable to date, and an effective encapsulation method is proposed to prevent the oxidation of Cu NWs electrode in the range of body temperatures.
Keywords: Body temperature; Copper nanowires; Electronics applications; Encapsulation methods; High temperature; High transparency; Oxidation behaviors; Wearable devices; Copper; Electrodes; Hot Temperature; Nanowires; Oxidation-Reduction; Wearable Electronic Devices; copper nanowires; flexible electronics; oxidation; wearable electronics